The gamification element selection method - Suepphong Chernbumroong (2019)
© 2019 IEEE. The Massive Open Online Course (MOOC) is considered as a new education platform which supports learners in accessing information anytime anywhere. However, the high dropout rate is still a crucial problem for MOOCs which is linked to the uncertainties of learner motivation. Thus, gamification can be a potential concept which promotes motivation and engagement for learners. Previously, many researchers already implemented game elements such as points, badges, or leaderboard in online learning contexts. The adaptation of different game elements provides different results. It seems that there is no empirical method which provides a guideline or suggestions on how to select such gamification elements. This paper provides a game element selection method for developers.